Organized labor and loan pricing: A regression discontinuity design analysis - Qiu, Yue; Shen, Tao (Journal of Corporate Finance, 2017)
This paper provides new evidence on the effect of unionization on the cost of bank loans. By using a regression discontinuity design, we establish a causal relation between new unionization and bank loan pricing. Relative to firms in which unions barely lose elections, firms in which unions barely win elections experience an increase in the spread of the newly originated loans. Further tests suggest that the effect of labor unions on the loan spread arises through the channel of reducing the recovery rate of banks in bankruptcy rather than increasing firms' default risk.